Molecular characterization and association of lactoferrin gene to subclinical mastitis in goats (Capra hircus) - Waminal, Yancy Ogdamin; Tubalinal, Gabriel Alexis San Pedro; Mingala, Claro Niegos (Acta Scientiarum. Animal Sciences, 2022)
The study characterized the lactoferrin (Lf) mRNA gene in different goat breeds in the Philippines and determined its association with subclinical mastitis (SCM). The study involved collection of milk at second week of lactation (n=75) and blood samples (n=5) to obtain extracted RNA and using cDNA to amplify Lf gene through polymerase chain reaction. The nucleotide and amino acid sequences were determined and used as reference in the evaluation of phylogenetic relationship. Amplified products were utilized for RFLP analysis before determining the association of the gene with SCM. Results of the study demonstrated that Lf gene in goats registered a molecular weight of 2135. Nucleotide and amino acid sequence of Lf gene revealed high similarity (99%) in Saanen, Anglo-Nubian and Philippine native goats with that of Capra hircus (U53857) Lf gene submitted to GenBank. Phylogenetic studies showed that Lf gene of Anglo-Nubian, Saanen and Native goats clade together with Lf gene of C. hircus (U53857). Three genotypes in goats were documented using the restriction enzymes AluI and HaeIII. Based on the Statistical analysis, association (comp 5.65, p = 0.0308) has been established between the Lf genes of goats with genotype BB to SCM using HaeIII restriction enzyme.